Use of polyetheretherketone (PEEK) in orbital floor fracture reconstruction – A case for concern. Issue 4 (July 2015) - Nazimi, Abd Jabar; Md Yusoff, Mazharul; Nordin, Rifqah; Nabil, Syed
Abstract In this unusual case report, we describe an adult patient who developed postoperative complication of vasovagal-like symptoms mimicking oculocardiac reflex (OCR) following secondary reconstruction of orbital floor blowout fracture utilizing computer generated, fully customized, patient-specific polyetheretherketone (PEEK) implant. Careful assessment with diagnosis and, if necessary, prompt treatment are critical to avoid complications that could lead to a life-threatening event. We discuss this rare postoperative event with emphasis given to the PEEK alloplastic material that is not commonly used in orbital floor reconstruction and its suggested precautions.